2010
DOI: 10.1162/rest_a_00004
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Innovation in Dutch Manufacturing: Is It Spurious?

Abstract: This paper studies the persistence of innovation and the dynamics of innovation output in Dutch manufacturing using firm data from three waves of the Community Innovation Surveys (CIS), pertaining to the periods 1994-1996, 1996-1998, and 1998-2000. We estimate by maximum likelihood a dynamic panel data type 2 tobit model accounting for individual effects and handling the initial conditions problem. We find that there is no evidence of true persistence in achieving technological product or process innovations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
190
2
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(206 citation statements)
references
References 36 publications
6
190
2
3
Order By: Relevance
“…Our main variables describing the founder characteristics have no variation over time within a firm. Hence, these variables would be wiped out when applying a fixed-effects estimator and we would not be able to identify the effects of the founder characteristics (see Raymond et al, 2010 for a detailed discussion on this issue). To deal with unobserved firm heterogeneity Innovation capability of firm founders Table 2 Estimates of innovative activity (random-effects probit) See Table 1 for the variable definitions; to estimate marginal effects, we fixed the group specific intercept at 0, but otherwise averaged the marginal effects over the other explanatory variables; SEs are in brackets under the coefficients.…”
Section: Heterogeneitymentioning
confidence: 99%
“…Our main variables describing the founder characteristics have no variation over time within a firm. Hence, these variables would be wiped out when applying a fixed-effects estimator and we would not be able to identify the effects of the founder characteristics (see Raymond et al, 2010 for a detailed discussion on this issue). To deal with unobserved firm heterogeneity Innovation capability of firm founders Table 2 Estimates of innovative activity (random-effects probit) See Table 1 for the variable definitions; to estimate marginal effects, we fixed the group specific intercept at 0, but otherwise averaged the marginal effects over the other explanatory variables; SEs are in brackets under the coefficients.…”
Section: Heterogeneitymentioning
confidence: 99%
“…Mañez et al (2009) study the persistence in the firm R&D status, i.e., in the decision to engage in R&D activities, while Peters (2009) analyzes whether firms innovate persistently, defining an innovator as a firm which exhibits positive innovation expenditure in a given year. In contrast to these studies, Duguet and Monjon (2004) and Raymond et al (2010) examine the persistence in innovation outputs, although, as they use CIS data, their indicators as to whether a firm has introduced an innovation are related to a 3-year period, which could induce an artificial persistence due to overlapping time periods and double counting (Peters, 2009). However, Raymond et al (2010) find that there is only true persistence of innovation in high-technology industries.…”
Section: Theoretical Framework and Empirical Modelmentioning
confidence: 99%
“…In contrast to these studies, Duguet and Monjon (2004) and Raymond et al (2010) examine the persistence in innovation outputs, although, as they use CIS data, their indicators as to whether a firm has introduced an innovation are related to a 3-year period, which could induce an artificial persistence due to overlapping time periods and double counting (Peters, 2009). However, Raymond et al (2010) find that there is only true persistence of innovation in high-technology industries. For low-technology industries, past process and product innovations and past shares of innovative sales do not affect current process and product innovations and innovative sales 2 .…”
Section: Theoretical Framework and Empirical Modelmentioning
confidence: 99%
“…Peters (2009) and Raymond et al (2009) found support for persistence of both innovation inputs and outputs. Raymond et al (2010) using a novel method to treat the initial conditions problem only confi rmed true persistence in the propensity of fi rms to innovate in the high-tech sector, while other results came out inconclusive. Earlier studies by Van Leeuwen (2002), Duguet and Monjon (2004) and Rogers (2004) found support for the persistence thesis but because of data constraints could not control for unobserved individual heterogeneity.…”
Section: Introductionmentioning
confidence: 95%